Heteroatom-modulated NiCo2O4 apparent energy activation of PMS for tetracycline removal: Mechanism and toxicity analysis - Pei, Yan; Liu, Xun; Cao, Mengbo; Wang, Zijun; Yang, Hongbing (Environmental research, 2024)
Heteroatom doping to reconfigure the electronic structure of heterogeneous catalysts is expected to lead to the development of advanced oxidation water purification materials with superior performance and greater stability. Herein, a series of catalysts with different elemental doping was developed by a simple and environmentally friendly one-step self-propagating combustion method to remove Tetracycline (TC). After S-doping, the normalized kinetic constant of TC was significantly increased from 30.49 to 159.41 min−1M−1 within 30 min, which is even higher than most recent heterogeneous catalysts. The prepared S-doped NiCo2O4 (NCO–S) exhibits an extremely promising catalytic performance for oxidation (92.8 %) and mineralization (65.9 %) of TC in a wide pH range (3–11). The resistance to interference is excellent for inorganic ions and even in real water samples. Quenching experiments, electron paramagnetic resonance (EPR), and electrochemical analyses demonstrated that the non-radical oxidation pathway, including electron transfer and 1O2, dominated the degradation process after S doping. It is speculated that possible intermediates and toxicological studies are discussed, finding that the overall degradation process is moving towards low toxicity to reveal prospects for large-scale applications. This work not only provides a way to remove TC, but may also inspire the design of more efficient and stable materials for water treatment and other applications. [Display omitted] •NCO–S was successfully prepared by a green and energy-saving self-propagation method.•S doping increased degradation performance of NiCo2O4 from 60.7 % to 99.4 %.•S doping promotes electron transfer and 1O2 generation.•The excellent normalized kinetics of S doping is more conducive to TC removal.